2018
DOI: 10.1111/cas.13635
|View full text |Cite
|
Sign up to set email alerts
|

IDH‐mutated astrocytomas with 19q‐loss constitute a subgroup that confers better prognosis

Abstract: IDH‐mutant gliomas are classified into astrocytic or oligodendroglial tumors by 1p/19q status in the WHO 2016 classification, with the latter presenting with characteristic morphology and better prognosis in general. However, the morphological and genetic features within each category are varied, and there might be distinguishable subtypes. We analyzed 170 WHO grade II‐IV gliomas resected in our institution. 1p/19q status was analyzed by microsatellite analysis, and genetic mutations were analyzed by next‐gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…OC86 carried PTCH1 mutation (Fig. 21 Six OCs included in our study carried 1p/19q co-deletion, as determined by NGS; the presence of this co-deletion was validated by appropriate PCR assay in five of these cases (Supplementary Information Tables S4 and S5). PTCH1 inactivation is frequently observed in basal cell carcinomas.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…OC86 carried PTCH1 mutation (Fig. 21 Six OCs included in our study carried 1p/19q co-deletion, as determined by NGS; the presence of this co-deletion was validated by appropriate PCR assay in five of these cases (Supplementary Information Tables S4 and S5). PTCH1 inactivation is frequently observed in basal cell carcinomas.…”
Section: Resultsmentioning
confidence: 76%
“…Combination of IDH2 mutation and 1p/19q co-deletion is characteristics for glioblastoma, although distinct hotspots for IDH1/2 amino acid substitutions are observed in brain tumors. 21 Six OCs included in our study carried 1p/19q co-deletion, as determined by NGS; the presence of this co-deletion was validated by appropriate PCR assay in five of these cases (Supplementary Information Tables S4 and S5). Some IDH2-mutated proteins, IDH2 p. R140Q, p.R172S and p.R172K, can be targeted by enasidenib, which has already been approved for the treatment of acute myeloid leukemia.…”
Section: Resultsmentioning
confidence: 84%
“…The presence of both IDH mutation and 1p/19q codeletion is associated with a more favorable clinical course, with improved sensitivity to procarbazine, lomustine, and vincristine chemotherapy and longer survival. 5,22,27 Therefore, a molecular classification might capture clinical behavior and prognosis more accurately than traditional histopathologic characteristics. 3 Consequently, due to the revised 2016 WHO classification of diffuse…”
Section: Discussionmentioning
confidence: 99%
“…5D). We further dissected the lower-grade glioma dataset into IDH-mutant astrocytoma and IDH-mutant ODG and found that astrocytoma patients, which have a shorter survival time (median survival=9-13 years 6,36 ), presented with lower SMPD3 transcript levels compared to ODG patients, which have a longer survival time (median survival= 12-14 years 40,41 ; Fig. 5E; p<0.0001) -suggesting that higher SMPD3 levels may reduce tumor growth.…”
Section: Lower Smpd3 Expression Is Associated With Poor Prognosis In mentioning
confidence: 99%
“…The most aggressive and most frequently studied is glioblastoma multiforme (GBM), a high-grade astrocytoma with 5-year survival rates of less than 5% 5 . In contrast, lower-grade gliomas (World Health Organization-WHO stage II/III tumors), which include oligodendroglioma (ODG), are slower growing tumors, with median survival times between 9-14 years 6 . Glioma subtypes each have a unique constellation of mutations, that in ODG typically includes isocitrate dehydrogenase 1 (IDH1) or IDH2 mutations, chromosomal 1p/19q co-deletion, and mutation of Capicua (CIC), a transcriptional repressor, in the retained 19q allele 7,8,9,10 .…”
Section: Introductionmentioning
confidence: 99%